Phytochemical Characterization, Bioactivities, and Nanoparticle-Based Topical Gel Formulation Development from Four Mitragyna speciosa Varieties - Pimporn Anantaworasakul; Weeraya Preedalikit; Phunsuk Anantaworasakul; Sudarshan Singh; Aekkhaluck Intharuksa; Warunya Arunotayanun; Mingkwan Na Takuathung; Songwut Yotsawimonwat; Chuda Chittasupho (Gels)
Mitragyna speciosa (kratom) is a traditional medicinal plant rich in bioactive alkaloids and phenolics, known for their antioxidant and anti-aging properties. This study aimed to develop nanoparticle-based topical gels from ethanolic extracts of four kratom varieties, including Kan Daeng (KD), Hang Kang (HK), Tai Bai-yao (KY), and Kan Keaw (KG). Kratom NPs were prepared using a solvent displacement method. The resulting nanoparticles (NPs) exhibited sizes of 201.9–256.2 nm, polydispersity indices (PDI) below 0.3, and a zeta potential between −22.6 and −29.6 mV. The phytochemical analysis revealed that KG and KY extracts contained the highest total phenolic content (TPC) and total flavonoid content (TFC), which were mostly retained after NP formulation. The HPLC analysis confirmed HK as the richest source of mitragynine (9.97 ± 0.10% w/w), while NP formulations displayed slightly reduced levels. Antioxidant activities assessed by DPPH, ABTS, and FRAP assays revealed enhanced radical scavenging in nanoparticle formulations, with IC50 values ranging from 151.23 to 199.87 µg/mL (DPPH) and 207.37 to 272.83 µg/mL (ABTS). All formulations exhibited a significant inhibition of collagenase (80.56 ± 1.60 to 97.23 ± 0.29%), elastase (45.46 ± 6.53 to 52.19 ± 1.20%), and hyaluronidase (83.23 ± 2.34 to 91.67 ± 3.56%), with nanoparticle forms showing superior enzyme inhibition. Notably, nanoparticle formulations exhibited superior inhibitory effects compared to crude extracts. HaCaT cytotoxicity tests confirmed high biocompatibility (IC50 > 700 µg/mL), especially for KD and KG NPs. The NP-loaded gels demonstrated acceptable physicochemical stability after heating/cooling cycle testing, with pH (7.27 to 7.88), viscosity (10.719 to 12.602 Pa·s), and favorable visual and textural properties. In summary, KG and KY cultivars emerged as the most promising cosmeceutical candidates due to their superior phytochemical content, antioxidant capacity, enzyme-inhibitory activities, and formulation performance. These findings support the potential use of KG NP and KY NP-loaded gels as multifunctional cosmeceutical agents for antioxidant protection, anti-aging, and skin rejuvenation.